2013
DOI: 10.12669/pjms.294.3176
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of ischemia-modified albumin in acute coronary syndrome and acute ischemic stroke

Abstract: Objective: To investigate diagnostic value of ischemia-modified albumin (IMA) levels in patients applying to emergency with symptoms of acute coronary syndrome (ACS) and acute ischemic stroke (AIS). Methods: Two patient groups (ACS and AIS) and a control group were constituted. The study was discontinued upon reaching 30 patients in each group. Following patient approval at the initial visit, a total of 10 ml venous blood sample was obtained from all patients with a high clinical suspicion of ACS and AIS. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
4
20
0
4
Order By: Relevance
“…It has been shown previously that IMA level estimated in blood serum sample has a prognostic value for acute ischemic stroke (40). Also, it is reported that IMA level increases in early ischemia and remains high (41). In our study, IMA was signifi cantly higher in the IR group than in the Control, Pregabalin 50 and 200 mg groups.…”
Section: Discussionsupporting
confidence: 53%
“…It has been shown previously that IMA level estimated in blood serum sample has a prognostic value for acute ischemic stroke (40). Also, it is reported that IMA level increases in early ischemia and remains high (41). In our study, IMA was signifi cantly higher in the IR group than in the Control, Pregabalin 50 and 200 mg groups.…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies have demonstrated that significantly higher IMA levels are found in patients with cardiac ischemia, metabolic syndrome, hyperlipidemia, and diabetes mellitus (7-10). Moreover, Ertekin et al (25) investigated the diagnostic value of IMA levels in patients with acute coronary syndrome and ischemic stroke symptoms and concluded that IMA could be a useful diagnostic marker in acute coronary syndrome and ischemic stroke. In a large series of breast cancer patients, IMA was regarded as a potential novel marker for diagnosing doxorubicin-induced myocardial injury by predicting long-term impairment of cardiac function (26).…”
Section: Discussionmentioning
confidence: 99%
“…Erken teşhis ve tedavi mortalite ve morbiditeyi azaltır (12) . AKS'nin gelişiminde farklı evrelerin saptanması için birçok kardiyak belirteç tarif edilmiştir.…”
Section: Akut Koroner Sendromunclassified
“…Klasik kardiyak biyokimyasal belirteçler yüksek duyarlılık ve spesifikliğe sahip olmakla birlikte bu belirteçlerin yükselişi ataktan saatler sonra olmaktadır. AKS'nin erken teşhisi için yeni çalışılan belirteçler kolin, İMA, kalp tipi yağ asiti bağlayıcı protein (H-FABP) ve N-terminal B tip natriüretik peptid (NT-proBNP)'dir (2,12) . Bunlardan yalnızca İMA rutin kullanım için lisanslı, duyarlı, ucuz ve iskemiyi erken saptamaktadır (2,4) .…”
Section: Akut Koroner Sendromunclassified
See 1 more Smart Citation